2022
DOI: 10.22616/rrd.28.2022.002
|View full text |Cite
|
Sign up to set email alerts
|

Formation of yield and quality of winter durum wheat grain depending on long-term fertilization

Abstract: Durum wheat (Triticum durum Desf.) grain is the main raw material for the production of high-quality pasta and cereal products. The research was conducted at Uman National University of Horticulture (Ukraine) in a long-term stationary experiment, founded in 2011. The aim of the work was to study the impact of long-term use of various fertilization systems (with incomplete return of nitrogen, phosphorus and potash fertilizers) on the yield and quality of durum winter wheat grain. The long-term application of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…An opposite effect was found in field trial in Latvia, where higher protein content was gained in minimal soil tillage system [27]. Scientists from Ukraine Hospodarenko and Liubych [7] reported that moisture deficiency and high temperature during the growth stage BBCH 73 in contributed to higher protein and gluten content in grain.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…An opposite effect was found in field trial in Latvia, where higher protein content was gained in minimal soil tillage system [27]. Scientists from Ukraine Hospodarenko and Liubych [7] reported that moisture deficiency and high temperature during the growth stage BBCH 73 in contributed to higher protein and gluten content in grain.…”
Section: Resultsmentioning
confidence: 93%
“…Higher average gluten content was observed when wheat was grown after field beans. Scientists from Uman National University of Horticulture, Ukraine Hospodarenko and Liubych [7] reported that the protein and gluten content are most dependent on weather conditions during grain maturation and the use of nitrogen fertilizers [7]. W-FB wheat after field beans; W-W wheat after wheat; W-W-W wheat in repeated sowings; MT -minimal soil tillage system; CT -conventional soil tillage system; significant at p<0.05.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations